Structural Features and Microwave Absorbing Properties of Polyaniline-Montmorillonite Composites Prepared by In-Situ (Journal of Fiber Bioengineering and Informatics, 2013)
Polyaniline (PANI)/montmorillonite (MMT) composites were prepared by in-situ polymerization ofaniline in the presence of MMT with ammonium persulfate (APS) and hydrochloric acid (HCl) as oxidantand acid dopant, respectively. PANI/MMT composites on structural properties were analyzed by FT-IR,XRD and SEM. The result of FT-IR analysis signified an interaction between PANI backbones and MMTlayer surfaces. X-ray diffraction showed an increase in the interlayer spacing of MMT, signifying PANIwas intercalated into the MMT galleries. PANI prepared in the presence of MMT exhibited flake-likemorphology rather than granular particle form of PANI without MMT. PANI/MMT10% showed higherelectrical conductivity than pristine PANI. PANI and PANI/MMT were separately used as the fillers toprepare paraffin composites and PANI/MMT10% had a better microwave absorbing performance thanPANI. The minimum reflection loss of PANI/MMT10%/paraffin composites with thickness of 8.0 mmwere -37 dB at 14.8 GHz and the effective absorption band under -10 dB was from 13 to 16 GHz.